Penggunaan Metode Technology Acceptance Model dalam Analisis E-Procurement di Pemprov Jawa Barat - Sarah Hana Fitriyah (Jurnal Riset Ilmu Ekonomi dan Bisnis, 2022)
Abstract. The government uses technology to reform public services into transparency and accountability through the creation of e-Government. An example of the application of e-Government is electronic procurement. However, there is a lack of unprepared human resources in the operation of e-Procurement which affects the effectiveness of e-Government. This research method is quantitative and descriptive using the Technology Acceptance Model (TAM). The population in this study is the Regional Apparatus/Bureau in West Java with a sample of 100 respondents. The analysis tool uses Partial Least Square SEM (PLS SEM). Researchers used the SmartPLS 3.0 software. Based on the results of the analysis, it is known that e-Procurement users in the West Java Provincial Government indicate that they have difficulty using e-Procuremen. Abstrak.Pemerintah menggunakan teknologi untuk mereformasi pelayanan publik menjadi transparansi dan akuntabilitas melalui penciptaan e-Government. Contoh penerapan e-Government adalah pengadaan secara elektronik. Namun, kurangnya terdapat masalah ketidaksiapan sumber daya manusia dalam pengoperasian e- Procurement yang mempengaruhi efektivitas e-Government. Metode penelitian ini adalah kuantitatif dan deskriptif dengan menggunakan Technology Acceptance Model (TAM). Populasi dalam penelitian ini adalah Perangkat Daerah/Biro di Jawa Barat dengan sampel sebanyak 100 responden. Alat analisis menggunakan Partial Least Square SEM (PLS SEM). Peneliti menggunakan software SmartPLS 3.0. Berdasarkan hasil analisis, diketahui bahwa pengguna e-Procurement di Pemerintah Provinsi Jawa Barat menunjukkan bahwa mereka mengalami kesulitan dalam menggunakan e-Procurement.